Iridium(III) Carbene Phosphors with Fast Radiative Transitions for Blue Organic Light Emitting Diodes and Hyperphosphorescence - Zheng, Zhong; Wang, Lu; Xin, Yangyang; Wang, Qi; Hong, Xiangchen; Zhang, Yuewei; Yiu, Shek‐Man; Zhou, Fan; Yan, Jie; Zhang, Dongdong; Duan, Lian; Chi, Yun (Advanced functional materials, 2025)
It is envisioned that the efficient and stable blue OLED phosphors can be synthesized using Ir(III) complexes with electron‐deficient carbene cyclometalates. Therefore, three facially coordinated Ir(III) phosphors f‐ct7a‐ c bearing isomeric purinylidene chelates are obtained. They possess three, two, and one 4‐t‐butylphenyl cyclometalate together with the same number of N‐phenyl appendage on carbene fragments, and exhibit photoluminescence centered (λmax) at 452‒461 nm, fast radiative rate constants (kr) of 7.5–11.3 × 105 s‒1, and high quantum yield (PLQY) up to 80% in degassed toluene at RT. Representative OLED based on f‐ct7c gives maximum external quantum efficiency (EQEmax) of 26.6%, CIE(x,y) of 0.16, 0.15, and low roll‐off with EQE of 22.3% at 1000 cd m‒2. Furthermore, they can be utilized to sensitize a deep blue multiple resonance thermally activated delay fluorescence emitter (MR‐TADF), i.e., t‐DABNA. The corresponding hyper‐OLED device based on alternative f‐ct7b realizes an EQEmax of 36.1%, CIE(x,y) of 0.14, 0.09, and full width at half maximum (FWHM) of 26.5 nm. To the understanding, this is the first report on concurrent achieving both the high EQE and small CIEy value for Ir(III)‐based phosphors. Blue Ir(III) phosphors f‐ct7a–c bearing purinylidene chelates are synthesized, among which the organic light‐emitting diode (OLED) based on f‐ct7c exhibits external quantum efficiency (EQEmax) 26.6% and EQE of 22.3% at 1000 cd m‒2, while hyper‐OLED based on f‐ct7b and t‐DABNA achieves EQEmax of 36.1% and CIE(x,y) of 0.14, 0.09.